2021
DOI: 10.3233/jad-210158
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Essential Metals with APOE Genotype in Alzheimer’s Disease

Abstract: Background: The major confirmed genetic risk factor for late-onset, sporadic Alzheimer’s disease (AD) is variant ɛ4 of apolipoprotein E gene (APOE). It is proposed that ApoE, a protein involved in transport of cholesterol to neurons can cause neurodegeneration in AD through interaction with metals. Previous studies mostly associated copper, iron, zinc, and calcium with ApoE4-mediated toxicity. Objective: To test the association of essential metals with APOE genotype. Methods: We compared plasma and cerebrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Our study therefore points at a TSC imbalance accompanying the neurodegenerative process in AD in vivo. This finding confirms observations from post mortem studies 18,26 and the recent detection of sodium increases in AD patients and subjects at risk 19,20 . Interestingly, TSC can be highly discriminative between control subjects and only mildly affected patients in temporal regions such as the fusiform gyrus and is predictive for cognitive state.…”
Section: Introductory Narrativesupporting
confidence: 87%
See 1 more Smart Citation
“…Our study therefore points at a TSC imbalance accompanying the neurodegenerative process in AD in vivo. This finding confirms observations from post mortem studies 18,26 and the recent detection of sodium increases in AD patients and subjects at risk 19,20 . Interestingly, TSC can be highly discriminative between control subjects and only mildly affected patients in temporal regions such as the fusiform gyrus and is predictive for cognitive state.…”
Section: Introductory Narrativesupporting
confidence: 87%
“…In the context of AD, baseline studies have indeed shown a close interplay between the pathological hallmarks of AD, that is, amyloid beta (Aβ) deposits and tau tangles with the NKA in disease models 13–16 . Correspondingly, sodium and potassium concentration imbalances have been detected in post mortem brain tissue, and increased sodium concentrations have also been found in blood plasma of AD patients and in cerebrospinal fluid (CSF) of those at risk 17–20 …”
Section: Introductionmentioning
confidence: 99%
“…This more widespread discriminative power of TSC outside the hippocampus could be due to the fact that disturbances in tissue homeostasis might precede the onset of significant atrophy. An increase in TSC has already been confirmed in post mortem examinations of brain tissue of AD patients ( Graham et al, 2015 , Vitvitsky et al, 2012 ) and in AD patients at risk ( Babić Leko et al, 2021 , Souza et al, 2020 ).…”
Section: Discussionmentioning
confidence: 67%
“…We did not choose e.g. the ventricles, since CSF sodium values have also recently been detected to change in AD-pathology and those at risk for it ( Babić Leko et al, 2021 , Souza et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the homeostasis of essential metals is altered in AD [ 26 , 27 , 28 ], where iron (Fe), zinc (Zn), and copper (Cu) are the essential metals most commonly associated with AD pathological changes. Heavy metal concentrations have also been found to rise in AD brains [ 29 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%